Manajemen Dalam Pengambilan Keputusan Di Gereja - Clara Raflesiane Misahapsari; Kalis Stevanus (Sekolah Tinggi Teologi Berita Hidup, 2022)
The organization is a forum for each institution and in certain fields to be able to create and implement every activity program. In the process of forming and implementing an activity, of course the organization uses management to organize and manage everything that is done through the existing organization. One of them is an organization in the church. The church uses management to manage and organize every activity it creates. Management carried out in the church is applied in various fields according to the needs of the church through a program created. One of them is management in the decisions made in the church. This management helps the pastor and the board or board that is there to be able to determine the best decision. In addition, through management in making decisions, the pastor and the existing board or council can resolve conflicts. However, until now there are still many churches that do not apply management in making decisions in various activities and fields in the church, so that many churches when they are still experiencing various conflicts without any good decisions. Therefore, the purpose of this article is to know the things that must be done in the application of management in decision making in the church. The method used in this writing is a qualitative descriptive method. From the writing of this article, the results obtained are that the pastor and church administrators or councilors can apply management in decision-making in the church to deal with existing conflicts and through a meeting.